2021
DOI: 10.1002/hep.31765
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA H19: A Key Player in Liver Diseases

Abstract: The role of lncRNA H19 in the regulation of liver development has been well documented. (8) Genetic and molecular studies have shown that H19 is a parentally imprinted and maternally expressed gene, which is localized to chromosome 7 in mice and chromosome 11p15.5 in humans, downstream

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…In addition, the mRNA levels of Acta2 and Col1a1 were dramatically increased in TGF-β-treated group, which were significantly reduced after FA treatment at medium and high doses ( Figure 4B ). We recently reported that the aberrant expression of long noncoding RNA (lncRNA) H19 was responsible for HSC activation and liver fibrosis progression in multiple mouse models ( Wang et al, 2021 ). As shown in Figure 4B , TGF-β-induced upregulation of H19 was significantly reversed by FA in LX-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the mRNA levels of Acta2 and Col1a1 were dramatically increased in TGF-β-treated group, which were significantly reduced after FA treatment at medium and high doses ( Figure 4B ). We recently reported that the aberrant expression of long noncoding RNA (lncRNA) H19 was responsible for HSC activation and liver fibrosis progression in multiple mouse models ( Wang et al, 2021 ). As shown in Figure 4B , TGF-β-induced upregulation of H19 was significantly reversed by FA in LX-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, further studies are needed to elucidate the role of lncRNA-H19 in non-alcoholic fatty liver (NAFLD) disease progression. 27 Whilst overexpression of lncRNA-H19 has been identified in tissue or plasma of various types of human cancers, including gastric, bladder, breast or pancreatic, 39 its role in HCC remains controversial. 26 In this study, lncRNA-H19 levels were significantly higher in patients with HCC versus cirrhotic patients at no risk of developing HCC (no cancer during follow-up).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA H19, which is firstly described as a fetal transcript in mice in 1984, is located on chromosome 11p15.5 and expressed exclusively from the maternal allele ( 131 , 132 ). Recent studies indicate that H19 is dysregulated in various cancer types and serves as oncogene or tumor suppressor to affect the development and progression of cancer through various mechanisms.…”
Section: H19/mir-194/pftk1mentioning
confidence: 99%